INTERNALISASI GLOBAL COMPACT FOR MIGRATION (GCM) DALAM MEMPERKUAT MEKANISME PERLINDUNGAN PEKERJA MIGRAN INDONESIA (PMI): STUDI KASUS IMPLEMENTASI DI P4MI BATAM - Rajagukguk, Rebecca Theresia Nauli; Takwa, Tuah Kalti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Indonesia's commitment to the international regime of the Global Compact for Migration (GCM), a United Nations (UN) agreement, is realized through the internalization of norms into national policies, particularly Law Number 18 of 2017. This study aims to analyze how these global norms, specifically Objective 6 of the GCM concerning ensuring decent working conditions, are operationally implemented by the Indonesian Migrant Worker Protection Service Post (P4MI) in Batam. This study employed qualitative methods, utilizing primary data through in depth interviews with P4MI Batam and several migrant workers there. It also utilized secondary data from books, journals, articles, websites, and official documents. The study results indicate that P4MI acts as a policy implementation unit, translating Objective 6 of the GCM into concrete protection mechanisms: Complaint Service Facilities, Handling of Problematic Migrant Workers, and coordinating prevention and case management with other agencies. However, P4MI still faces challenges and obstacles in implementing these efforts, such as limited capacity from both internal and external factors, as well as the perception that official channels are complicated and time-consuming. Keywords: P4MI Batam, Objective 6 of GCM, Protection of Indonesian Migrant Workers, Neoliberal Institutionalism